Tradisi Lubuk Larangan sebagai Wujud Kearifan Lokal dalam Mendukung Pelestarian Ekosistem Perairan di Desa Salak, Kecamatan Talawi - Indra Yeni; Khoirunnisya Simbolon; Keysa Rieza Chaniago; Fauzia Azima; Wizaldi; Muhammad Rafi Ramadan (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Lubuk Larangan Tradition Research is one of the forms of local wisdom that develops in the Salak Village community, Talawi District, which aims to maintain the balance of the aquatic ecosystem sustainably. In practice, the community jointly designated the Batang Ombilin river area as an area that is prohibited from catching fish for a certain period of time. At the agreed time, residents are allowed to fish as a form of celebration and utilization of conservation results. This research aims to describe and analyze the local values contained in the Lubuk Larangan tradition and its contribution to environmental preservation and community socio-economic empowerment. The method used in this study is a descriptive qualitative approach with direct observation techniques, interviews with community figures and documentation of activities during the implementation of tradition. Research results show that Lubuk Larangan not only functions as a community-based conservation strategy, but also becomes a means of strengthening social solidarity, environmental education, and additional economic resources for residents. This tradition reflects the harmonious relationship between humans and nature that has been passed down from generation to generation. Therefore, the preservation and strengthening of the Lubuk Larangan tradition needs to continue to be encouraged as a model for sustainable natural resource management.